Token-Aware API Design Patterns for Model Context Protocol Integration in Enterprise Distributed Systems - Nikhil Bharadwaj Ramashasthri (International Journal of Engineering, Science and Information Technology, 2026)
Autonomous software agents operating through the Model Context Protocol (MCP) reveal a fundamental architectural mismatch between conventional REST API design and the finite context windows of Large Language Model (LLM) inference engines. Enterprise backend services originally optimized for browser-based applications typically return payloads enriched with deeply nested relational structures, verbose infrastructure metadata, and redundant serialization artifacts. While acceptable for human-operated interfaces, these responses unnecessarily consume LLM context capacity when delivered through MCP servers, increasing inference costs, reducing reasoning efficiency, and limiting the number of actionable interactions that autonomous agents can perform. This article investigates serialization-boundary optimization as a critical architectural concern for MCP-native systems and proposes four composable backend design patterns: Semantic Envelope, infrastructure metadata pruning, dynamic token-aware pagination, and GraphQL interface projections. Together, these patterns restructure API responses to maximize semantic density while minimizing token consumption without modifying underlying domain models or persistence layers. The implementation is demonstrated in enterprise environments built on Spring Boot and Hibernate, illustrating seamless integration with existing software architectures. Experimental evaluation using production entity structures from a peer-to-peer car-sharing marketplace processing millions of vehicle transactions annually shows token reductions ranging from 34% to 86% across the proposed patterns, a 40% decrease in API pagination cycles, and a 97% reduction in response latency through a two-tier semantic caching strategy deployed over an 11.5-million-row persistence layer sustaining approximately 48,900 read operations per minute. These findings demonstrate that context-aware serialization significantly improves LLM agent efficiency while preserving enterprise scalability, interoperability, and maintainability. The proposed framework provides a practical engineering vocabulary and reference architecture for designing token-efficient, MCP-native backend systems capable of supporting the next generation of autonomous AI agents in large-scale enterprise environments.